The Financial Distress of Corporate Personality: A Perspective from Fiqh - Busari, Saheed Abdullahi; Zakariyah, Luqman; Amanullah, Muhammad; Abdul Aziz, Akhtarzaitie (2019)
Oriental scholars discuss the concept of corporate personality without any reference to Islamic law. A leading proponent of this view is Joseph Schacht; a western scholar of jurisprudence who contended that Islamic jurisprudence is limited to individual personality and devoid of corporate laws, hence, contractual agreements between corporations has no basis in Islamic law. Several scholars and researcher have responded with sufficient literature on the status of an artificial person in Islamic law, but there are still issues with the legal implication of corporate personality in the event of financial distress. This study aims to explore Islamic threshold on fundamental principles of corporate personalities and its contemporary applications in the situation of financial trouble. The study will employ the analytical approach in describing the essential characteristics of a corporation as inherent in Islamic law through interpolation from the natural person and the possibility of adapting the existing conventional bankruptcy laws. This study employs an analytical approach to Islamic literature and regular related works. The study found out that even though the concept of financial distress has basis in Islamic law, it remains complicated as it entails insolvency, bankruptcy and interdiction in a debtor creditor relationship. Overall, further efforts need to be done to put these concepts into contemporary and applicable perspectives without violating Islamic fundamental principle of justice and fair dealings.